Cholesterol-lowering effects and potential mechanisms of different polar extracts from Cyclocarya paliurus leave in hyperlipidemic mice. (24th December 2015) - Jiang, Cuihua; Wang, Qingqing; Wei, YuJian; Yao, Nan; Wu, Zhengfeng; Ma, Yonglan; Lin, Zi; Zhao, Ming; Che, Chuntao; Yao, Xiaoming; Zhang, Jian; Yin, Zhiqi
Abstract: Ethnopharmacological relevance: Cyclocarya paliurus Batal., native only to China, is widely consumed as a Chinese traditional folk medicine for the prevention and treatment of hyperlipidemia, obesity, and diabetes. The aim of the study is to investigate the cholesterol-lowering effect and potential mechanisms of different polar extracts from Cyclocarya paliurus leaves in mice fed with high-fat-diet. Materials and methods: Cyclocarya paliurus leaves extracts were orally administered to diet-induced hyperlipidemic mice for 4 weeks. Simvastatin was used as a positive control. Body weight, food intake, histopathology of liver and adipose tissues, hepatic and renal function indices, lipid profiles in the serum and liver were evaluated. Total bile acid concentrations of the liver and feces were also measured. Furthermore, the activities and mRNA expression of cholesterol metabolism-related enzymes including 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, cholesterol 7α-hydroxylase (CYP7A1) and acyl-CoA cholesterol acyltransferase 2 (ACAT2) in the livers of the mice were analyzed. LC–MS detection was performed to identify the components in the active fraction of Cyclocarya paliurus extracts. Results: Different Cyclocarya paliurus polar extracts, especially ChE reduced the levels of serum total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C) and hepatic TC and TG, enhanced the level of serum high-density lipoprotein cholesterol (HDL-C), restored hepatic and renal function indices and histomorphology. HMG-CoA reductase activity and mRNA expression were decreased, while CYP7A1 activity and mRNA expression as well as the level of fecal and hepatic bile acid were increased by ChE. LC–MS analysis of ChE revealed the presence of six main triterpenoids, which might be responsible for its antihyperlipidemic bioactivity. Conclusions: Evidently ChE possesses the best antihyperlipidemic activity, and the cholesterol-lowering effect is at least partly attributed to its role in promoting the conversion of cholesterol into bile acids by upgrading the activity and mRNA expression of CYP7A1 and inhibiting those of HMG-CoA reductase to lower the cholesterol biosynthesis. Graphical abstract: